Political Islam, European Muslim and Terrorism Issues: A Reflection - Herdi Sahrasad; Ibnu Rusyd (Budapest International Research and Critics University, 2021)
In the period 2014-2015, the European Union was shaken by the influx of migrants from the Middle East, North Africa, and the Balkans (Eastern Europe) who increasingly flooded the western region of the white continent. In a March 2015 report, UNHCR said the conflicts in Iraq and Syria brought the number of asylum seekers in Western countries in 2014 to the highest level in 22 years. There were an estimated 866,000 asylum seekers in 2014. That number is a 45 percent increase compared to 2013. And, during the 2014-16 refugee crisis from the Middle East and Africa, millions of refugee flows from the Middle East and Africa were rejected. In this regard, Olivier Roy sees that in Europe itself there is a danger of radical Islamism, a Muslim terrorism movement that undermines European peace and undermines Western trust on Muslim communities and political Islam. This paper explains Roy's perspective and Islamic radicalism in Europe which does not benefit the position and image of Muslims in Europe and the West in general.